Cathodic stripping voltammetric determination of 2-mercaptobenzothiazole using the catalytic cobalt peak - Fogg, Arnold G.; Ismail, Razali; Ahmad, Rahmalan; Banica, Florin G. (Elsevier, 1997)
Previously, thiols have been determined indirectly by cathodic stripping voltammetry (CSV) after accumulation as their mercury and copper(I) salts. Following a previous report of the first use of the catalytic nickel peak (for the determination of cysteine), this paper reports the first use of the catalytic cobalt peak in CSV (for the determination of 2-mercaptobenzothiazole (MBT)): only a very ill-defined catalytic cobalt peak had been observed previously with cysteine, and was unreported. MBT is accumulated at pH 4 (Britton-Robinson buffer) as its cobalt(II) complex at −0.1 V, and is then determined indirectly by observing the reduction of the cobalt(II) in the complex at −0.95 V, i.e., with a much lowered overpotential: hydrated cobalt(II) is reduced at −1.2 V. The peak is catalytic because the thiol released on reduction of the complex complexes further cobalt ions and causes their reduction. The detection limit for the determination of MBT was calculated to be 2.5 × 10−9 M (3σ) using an accumulation time of 1 min. The sensitivity is about three times that obtained with the corresponding catalytic nickel peak.